Highly efficient and stable hole-transport-layer-free inverted perovskite solar cells achieved 22% efficiency through p-type molecular synergistic doping. (15th December 2022) - Zhou, Xianyong; Zhang, Luozheng; Hu, Hang; Jiang, Zhengyan; Wang, Deng; Chen, Jiabang; Li, Yaru; Wu, Jiawen; Zhang, Yong; Zhang, Meiqing; Liu, Chang; Peng, Yuanjun; et al.
Abstract: low-cost, facile manufacturing processes are becoming more and more important for commercialization of perovskite solar cells (PSCs). In this aspect, the development of hole-transport-layer-free (HTL-free) PSC is particularly important. In this paper, we fabricated HTL-free PSC with improved photovoltaic performance via synergistic doping Cu(thiourea)Cl (Cu(Tu)Cl) and thiosemicarbazide into the perovskite precursor solution to obtain high-quality perovskite films with average grains of more than 1 µm. This synergistic doping strategy can simultaneously decrease perovskite surface and internal defects and mitigate interfacial energy barrier, which is superior to the present single passivation method which brings about defect passivation deficiency. As a result, compared to the control device with the efficiency of 13.10%, the HTL-free perovskite device prepared by synergistic doping strategy achieves a remarkable PCE of 22% with almost negligible hysteresis, which is the highest PCE values reported so far for the HTL-free PSCs. In addition, the environmental, thermal and long-term operational stabilities of the optimized devices prepared by synergistic doping strategy are significantly improved compare to the control devices. Especially, the unencapsulated optimized device retains 90% of the original efficiency under continuous illumination (100 mW cm −2 ) for 1000 h with the maximum power point (MPP) tracking in nitrogen-filled test box. Furthermore, this strategy has been shown to be effective in wide-bandgap perovskite. The wide-bandgap perovskite Cs0.05 MA0.15 FA0.8 Pb(I0.75 Br0.25 )3 (1.65 eV) based HTL-free device achieves a PCE of 19.7% with an Voc of 1.2 V, which is the highest PCE values reported so far for the HTL-free wide-bandgap PSCs, which opens a new way to fabricate HTL-free perovskite-based tandem solar cells. This work manifests a noteworthy step towards the facile, cost-efficient fabricating of PSCs with both high efficiency and simple manufacturing processes. Graphical Abstract: A good additive strategy that introducing p-type semiconductor molecule Cu(Tu)Cl and TSC into the perovskite films to eliminate the hole-transport-layer from device construction is demonstrated. Cu(Tu)Cl and TSC-doped the perovskite films show about micrometer-sized grains, full surface coverage, and ameliorated crystallinity. As a result, the hysteresis-free, best PCE of 22% with an Voc of 1.16 V was achieved in the hole-transport-layer-free inverted PSCs. ga1 Highlights: A novel synergistic doping strategy to further enhance the efficiency of hole-transport-layer-free perovskite solar cells by adding Cu(thiourea)Cl and thiosemicarbazone into the perovskite precursor solution. This synergistic doping strategy can simultaneously decrease perovskite surface and internal defects and mitigate interfacial energy barrier, which is superior to the present single passivation method which brings about defect passivation deficiency. The efficiency of hole-transport-layer-free PSCs was enhanced from 13.10% to 22%, accompanied with excellent stability, which is the highest PCE value reported so far for the hole-transport-layer-free PSCs. This strategy has been shown to be effective in wide-bandgap perovskite, the wide-bandgap perovskite Cs0.05 MA0.15 FA0.8 Pb(I0.75 Br0.25 )3 (1.65 eV) based HTL-free device achieves a PCE of 19.7% with an Voc of 1.2 V.